1997
DOI: 10.1076/ceyr.16.9.857.5039
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C in human and guinea pig aqueous, lens and plasma in relation to intake

Abstract: Plasma and aqueous appear to be saturated in humans with intakes of < 250 mg vitamin C/day. However, a saturating relationship between lens vitamin C and dietary intake in humans was not indicated in this study, although such a relationship is seen in guinea pigs. Intertissue relations between vitamin C levels in humans and guinea pigs are similar for some but not all relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 15 publications
5
36
2
1
Order By: Relevance
“…This finding is important since it shows that it is possible to alter the lenticular ascorbate concentration with dietary intake. The linear dependence of lens ascorbate concentration on dietary intake in the rat reported in this study is different from the dependence reported in the guinea pig [36]. In the guinea pig, the increase is nonlinear and saturable.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This finding is important since it shows that it is possible to alter the lenticular ascorbate concentration with dietary intake. The linear dependence of lens ascorbate concentration on dietary intake in the rat reported in this study is different from the dependence reported in the guinea pig [36]. In the guinea pig, the increase is nonlinear and saturable.…”
Section: Discussioncontrasting
confidence: 55%
“…The method of HPLC with UVR detection has been used for over a decade to analyze ascorbate from a number of tissues and plasma [34]. HPLC with electrochemical detection has been applied to measure ascorbate in the lens tissue from Emory mice [35], guinea pigs and humans [36]. We decided to apply the technique of HPLC with UVR detection to ascorbate measurement in rat lens samples processed and purified using ultrafiltration.…”
Section: Measurement Of Ascorbatementioning
confidence: 99%
“…These data are consistent with the prior observation that human eye tissues saturate at intakes of vitamin C between 200 and 300 mg/d. 41 The intake data are also supported by our plasma measures that suggest a lower prevalence of nuclear opacification with increasing plasma ascorbic acid concentrations.…”
Section: Plasma Nutrients and Prevalence Of Opacitiesmentioning
confidence: 50%
“…Previous studies show that ascorbic acid concentrations are much higher in aqueous humor than in plasma [12, 13]. This concentration gradient is a result of active transport in the ciliary epithelium [14].…”
Section: Discussionmentioning
confidence: 99%